Use patterns, use values and management of Afzelia africana Sm. in Burkina Faso: implications for species domestication and sustainable conservation - Balima, L.H.; Nacoulma, B.M.I.; Ekue, M.R.M.; N’Guessan Kouame, F.N.; Thiombiano, Adjima (Springer, 2018)
Background: The lack of literature on the interactions between indigenous people and the valuable agroforestry trees hinder the promotion of sustainable management of plant resources in West African Sahel. This study aimed at assessing local uses and management of Afzelia africana Sm. in Burkina Faso, as a prerequisite to address issues of domestication and sustainable conservation. Methods: One thousand forty-four peoples of seven dominant ethnic groups were questioned in 11 villages through 221 semi-structured focus group interviews. The surveys encompassed several rural communities living around six protected areas along the species distribution range. Questions refer mainly to vernacular names of A. africana, locals’ motivations to conserve the species, the uses, management practices and local ecological knowledge on the species. Citation frequency was calculated for each response item of each questionnaire section to obtain quantitative data. The quantitative data were then submitted to comparison tests and multivariate statistics in R program. Results: A. africana is a locally well-known tree described as a refuge of invisible spirits. Due to this mystery and its multipurpose uses, A. africana is conserved within the agroforestry systems. The species is widely and mostly used as fodder (87.55%), drugs (75.93%), fetish or sanctuary (70.95%), food (41.49%), and raw material for carpentry (36. 19%) and construction (7.05%). While the uses as fodder, food and construction involved one organ, the leaves and wood respectively, the medicinal use was the most diversified. All tree organs were traditionally used in 10 medical prescriptions to cure about 20 diseases. The species use values differed between ethnic groups with lower values within the Dagara and Fulani. The findings reveal a total absence of specific management practices such as assisted natural regeneration, seeding, or transplantation of A. africana sapling. However, trees were permanently pruned and debarked by local people. Harvesting of barks mostly contributed to the decline of the species populations. Local people acknowledged declining populations of A. africana with lower densities within the agroecosystems. They also perceived between individuals, variations in the traits of barks, leaves, fruits and seeds. Significant differences were found between ethnic groups and gender regarding the species uses. Local knowledge on the species distribution differed between ethnic groups. Conclusion: This study showed the multipurpose uses of A. africana throughout Burkina Faso. The results provide relevant social and ecological indicators to all stakeholders and constitute a springboard towards the species domestication and the elaboration of efficient sustainable conservation plans.